Exchange Traded Funds (ETFs) and Price Discovery in Equity Markets: Empirical Evidence from Developed and Emerging Markets - Deepak Kumar Prasad (Researchers World - International Refereed Social Sciences Journal, 2025)
Purpose: This paper investigates the price discovery relationship between exchange-traded funds (ETFs) and their underlying equity baskets across developed and emerging markets, with a focused empirical module on Indian equity ETFs listed on the National Stock Exchange (NSE) and Bombay Stock Exchange (BSE) under SEBI’s regulatory framework. Using intraday trade and quote data spanning 2010 to 2024 across the United States (NYSE/Nasdaq), Europe (Euronext, LSE), Japan (JPX), Hong Kong (HKEX), and India (NSE/BSE), we estimate price discovery metrics Hasbrouck (1995) information share (IS), Gonzalo and Granger (1995) component share (CS), and Putniņš (2013) information leadership share (ILS) derived from vector error correction models (VECMs) applied to synchronised intraday ETF and synthetic NAV series. We document that ETFs lead price discovery more often than the underlying basket in liquid, developed markets, particularly when the constituent basket is costly or slow to trade. In emerging markets, and specifically in India, we find a more nuanced picture: the relative leadership of the ETF depends heavily on the trading hour, the availability of authorised participant arbitrage capacity, and prevailing bid-ask spreads in constituent stocks. We identify causal effects using event studies around creation/redemption activity, large premium/discount episodes, and regulatory transparency shocks including the SEC’s ETF Rule (Rule 6c-11, 2019) and SEBI’s successive ETF circulars. Cross-sectional panel regressions confirm that ETF liquidity, basket illiquidity, and flow shocks are the primary determinants of ETF-led price discovery. These findings have direct implications for ETF market design, disclosure policy, and investor trading strategy in both advanced and developing equity markets.